2008
DOI: 10.2753/res1060-9393500101
|View full text |Cite
|
Sign up to set email alerts
|

Family and Children in the Attitudes and Life Plans of Russians

Abstract: Specialists in the field of family research emphasize that the history of the family in Russia, as in all other countries of the world, is closely linked to the social, economic, and political processes of the modernization of society. The general vector of the development of the institution of the family, under the influence of processes of modernization, is linked to the establishment of particular social relations and forms of the organization of life, to a stronger orientation toward the individuation of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Although the fact that the Russians living in Estonia were less collectivistic with regard to families and society than the Russians from Moscow corroborates the general rule that those who have migrated to other countries are usually more individualistic than those who have stayed in their resident countries. The Russian family values also dominated over the values of the individualism (Varlamova, Noskova, & Sedova, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Although the fact that the Russians living in Estonia were less collectivistic with regard to families and society than the Russians from Moscow corroborates the general rule that those who have migrated to other countries are usually more individualistic than those who have stayed in their resident countries. The Russian family values also dominated over the values of the individualism (Varlamova, Noskova, & Sedova, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers allege that young people in postcommunist societies have become demoralized, hopeless, and desperate, and that they have abandoned all moral standards (see Roberts, 2003). Other surveys, however, qualify this very pessimistic view (Varlamova, Noskova, & Sedova, 2008). For example, despite some change, studies reveal stability in many core traditional values (Boski, 1994; Cieciuch, 2007; Varlamova et al., 2008), and the degree to which young people endorse materialism is a function of the macroeconomic situation.…”
Section: Social Change and Developmental Tasks In Adolescencementioning
confidence: 99%
“…Other surveys, however, qualify this very pessimistic view (Varlamova, Noskova, & Sedova, 2008). For example, despite some change, studies reveal stability in many core traditional values (Boski, 1994;Cieciuch, 2007;Varlamova et al, 2008), and the degree to which young people endorse materialism is a function of the macroeconomic situation. Further, Olson et al (2006) showed that simply wanting a job with good financial returns is associated with poorer economic conditions, whereas wanting a career for intrinsic reasons is associated with a country's economic prosperity.…”
Section: Values As Guide To Behaviormentioning
confidence: 99%
See 1 more Smart Citation
“…The stability of existing marriages weakens from generation to generation (Zakharov & Churilova, 2013;Popova & Barashkova, 2014;Novoselova, 2016); the number of extramarital births is growing (Plotnick, 1993;Hartmann, 1995;Martin & Thery, 2001;Popova, 2007;Churilova, 2018). All of the above is a basis for transformations in the human value system (Varlamova, Noskova, & Sedova, 2006;Lapin, 2010;Arkhangelsk, 2013;Mareeva, 2013;Dobrohleb & Zvereva, 2016;Sukneva & Barashkova, 2016).…”
Section: Introductionmentioning
confidence: 99%